Global challenges and local solutions: A cross-country comparative perspective on teaching legal English - Katarzyna Mroczyńska; Tomasz Michta (Studia z Teorii Wychowania)
The established role of English as a legal lingua franca has led to a growing demand for legal English education, presenting a unique set of challenges. Although these challenges are global, they call for local solutions, tailored to the specific needs of students This article draws on available accounts of teaching legal English at the tertiary level in the UK, the USA, Israel and Poland to offer a cross-country perspective on these challenges and the adopted strategies. The article concludes that legal English students form a highly heterogenous group with varying needs. This state of affairs influences the organization of legal English courses, the materials used, and the responsibilities of teachers.